Potential economic consequences of a cardioprotective agent for patients with myocardial infarction: modelling study. Issue 11 (13th November 2015) - Verhoef, Talitha I; Morris, Stephen; Mathur, Anthony; Singer, Mervyn
Abstract : Objective: To investigate the cost-effectiveness of a hypothetical cardioprotective agent used to reduce infarct size in patients undergoing percutaneous coronary intervention (PCI) after anterior ST-elevation myocardial infarction. Methods: Design : A cost-utility analysis using a Markov model. Setting : The National Health Service in the UK. Patients : Patients undergoing PCI after anterior ST-elevation myocardial infarction. Interventions : A cardioprotective agent given at the time of reperfusion compared to no cardioprotection. We assumed the cardioprotective agent (given at the time of reperfusion) would reduce the risk and severity of heart failure (HF) after PCI and the risk of mortality after PCI (with a relative risk ranging from 0.6 to 1). The costs of the cardioprotective agent were assumed to be in the range £1000–4000. Main outcome measures : The incremental costs per quality-adjusted life-year (QALY) gained, using 95% CIs from 1000 simulations. Results: Incremental costs ranged from £933 to £3820 and incremental QALYs from 0.04 to 0.38. The incremental cost-effectiveness ratio (ICER) ranged from £3311 to £63 480 per QALY gained. The results were highly dependent on the costs of a cardioprotective agent, patient age, and the relative risk of HF after PCI. The ICER was below the willingness-to-pay threshold of £20 000 per QALY gained in 71% of the simulations. Conclusions: A cardioprotective agent that can reduce the risk of HF and mortality after PCI has a high chance of being cost-effective. This chance depends on the price of the agent, the age of the patient and the relative risk of HF after PCI.